2006
DOI: 10.1021/jp0656532
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Germanium Oxynitride as a Photocatalyst for Overall Water Splitting under Visible Light

Abstract: A solid solution of zinc oxide and germanium nitride (Zn 1+x Ge)(N 2 O x ) (x ) 0.44) is demonstrated to be an effective photocatalyst for overall water splitting under ultraviolet and visible light. The catalyst is prepared by reaction of GeO 2 and ZnO under ammonia flow (20 mL‚min -1 ) at 1123 K for 15 h. The crystal structure of the material is investigated by a combination of Rietveld analysis and the maximum-entropy method using neutron powder diffraction data. The (Zn 1.44 Ge)(N 2.08 O 0.38 ) catalyst is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
217
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(223 citation statements)
references
References 34 publications
5
217
0
1
Order By: Relevance
“…189 A solid solution of zinc oxide and germanium nitride (Zn 1+x Ge)(N 2 O x ) (x = 0.44) was later demonstrated to be an effective photocatalyst for overall water-splitting under ultraviolet and visible light. 193 The catalyst was prepared by reacting GeO 2 and ZnO under ammonia flow at 1123 K for 15 h. 193 Rh 2Àx Cr x O 3 was identified as the most effective co-catalyst for (Zn 1+x Ge)(N 2 O x ), which greatly caused an increase in the activity for hydrogen evolution. Modification of the optimized (Zn 1.44 Ge)(N 2.08 O 0.38 ) sample by loading with Rh 2Àx Cr x O 3 (3.0 wt% Rh, 0.2 wt% Cr) results in an effective photocatalyst for overall water decomposition with a quantum efficiency of ca.…”
mentioning
confidence: 99%
“…189 A solid solution of zinc oxide and germanium nitride (Zn 1+x Ge)(N 2 O x ) (x = 0.44) was later demonstrated to be an effective photocatalyst for overall water-splitting under ultraviolet and visible light. 193 The catalyst was prepared by reacting GeO 2 and ZnO under ammonia flow at 1123 K for 15 h. 193 Rh 2Àx Cr x O 3 was identified as the most effective co-catalyst for (Zn 1+x Ge)(N 2 O x ), which greatly caused an increase in the activity for hydrogen evolution. Modification of the optimized (Zn 1.44 Ge)(N 2.08 O 0.38 ) sample by loading with Rh 2Àx Cr x O 3 (3.0 wt% Rh, 0.2 wt% Cr) results in an effective photocatalyst for overall water decomposition with a quantum efficiency of ca.…”
mentioning
confidence: 99%
“…1b) and CoO x (Fig. 1c), the peak position of AgTaO 3 did not change, which indicated that Pt and CoO x were just deposited on the surface instead of being inserted in the crystal lattice of AgTaO 3 . No peaks derived from Pt and CoO x were observed.…”
Section: Water-splitting Reactionsmentioning
confidence: 94%
“…To date, a considerable number of photocatalysts have been developed to construct water splitting systems including one-step [2][3][4][5][6][7][8][9][10][11] and two-step 12-17 photoexcitation systems. However, in both systems, the water oxidation process is currently considered to be a key bottleneck in water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…Among various interesting reactions, the splitting of water into molecular hydrogen and molecular oxygen by visible light is potentially one of the most promising ways for the photochemical conversion and storage of solar energy Lee et al 2007;Bard 1979;Sayama et al 2001). Since the first reported photo splitting of water by Fujishima and Honda in 1972 many authors have published their efforts to split water using semiconductor photocatalysis (Bolton 1996;Esswein and Nocera 2007;Kudo and Miseki 2009;Amouyal 19995).…”
Section: Historical Overview Of Water Splittingmentioning
confidence: 99%
“…As previously discussed, the photocatalyst employed should have a suitable thermodynamic potential for H 2 O splitting, a sufficiently narrow band gap to harvest visible photons, and stability against photocorrosion. These requirements are rather stringent and thereby limit the number of photocatalysts capable of photosplitting H 2 O using the one step mechanism Lee et al 2007). Discussed here is the two-step Z-scheme mechanism for H 2 O splitting, Figure 13.…”
Section: Z-scheme Photocatalystsmentioning
confidence: 99%